Phosphatidylcholine (18:0/20:4), a potential biomarker to predict ethionamide‐induced hepatic steatosis in rats. Issue 9 (29th March 2022) - Muta, Kyotaka; Saito, Kosuke; Kemmochi, Yusuke; Masuyama, Taku; Kobayashi, Akio; Saito, Yoshiro; Sugai, Shoichiro
Abstract: Ethionamide (ETH), a second‐line drug for multidrug‐resistant tuberculosis, is known to cause hepatic steatosis in rats and humans. To investigate predictive biomarkers for ETH‐induced steatosis, we performed lipidomics analysis using plasma and liver samples collected from rats treated orally with ETH at 30 and 100 mg/kg for 14 days. The ETH‐treated rats developed hepatic steatosis with Oil Red O staining‐positive vacuolation in the centrilobular hepatocytes accompanied by increased hepatic contents of triglycerides (TG) and decreased plasma TG and total cholesterol levels. A multivariate analysis for lipid profiles revealed differences in each of the 35 lipid species in the plasma and liver between the control and the ETH‐treated rats. Of those lipids, phosphatidylcholine (PC) (18:0/20:4) decreased dose‐dependently in both the plasma and liver. Moreover, serum TG‐rich very low‐density lipoprotein (VLDL) levels, especially the large particle fraction of VLDL composed of PC containing arachidonic acid (20:4) involved in hepatic secretion of TG, were decreased dose‐dependently. In conclusion, the decreased PC (18:0/20:4) in the liver, possibly leading to suppression of hepatic TG secretion, was considered to be involved in the pathogenesis of the ETH‐induced hepatic steatosis. Therefore, plasma PC (18:0/20:4) levels are proposed as mechanism‐related biomarkers for ETH‐induced hepatic steatosis. Abstract : Lipidomics analysis was performed in the plasma and liver of ETH‐treated rats to investigate biomarkers for ETH‐induced hepatic steatosis. The ETH‐treated rats showed a dose‐dependent decrease in PC (18:0/20:4) in the plasma and liver and hepatic steatosis with a decrease in serum TG‐rich VLDL levels. In conclusion, plasma PC (18:0/20:4) levels are proposed as mechanism‐related biomarkers for ETH‐induced hepatic steatosis.